Job Stress and Work-Family Conflict: Moderating role of mentoring in Call Center Industry - Vivek Sharma; Ajay Kumar Chalotra; Dada Ab Rouf Bhat (International Journal of Early Childhood Special Education, 2022)
The primary purpose of this study is to examine the relationship between job stress and work-family conflict. The study also examines the moderating role of mentoring between job stress and work-family conflict. The purposive sampling technique has been used to collect the data from five domestic call centers operating in Gurugram (NCR, New Delhi). The data was examined using Exploratory factor analysis (EFA), confirmatory factor analysis (CFA) followed by Structured Equation Modeling (SEM) to check the relationship between the hypothesis. Results revealed a significant relationship between job stress and work-family conflict. Employees who work long hours having too much work stress are more inclined to have work-family conflicts. Moreover, it was observed that mentoring acts as a moderator between job stress and work-family conflict. The study is limited to only five domestic call centers in Gurugram. Future studies should include international call centers across India for more generalized results.
Keywords: 330; Job stress; Mentoring; and; Work-family conflict; Performance